Recurrent facial urticaria following herpes simplex labialis - Vijay Zawar; Kiran Godse (Wolters Kluwer Medknow Publications, 2012)
We describe recurrent acute right-sided facial urticaria associated with herpes labialis infection in a middle-aged female patient. Antiviral medications and antihistamines not only successfully cleared the herpes infection and urticaria but also prevented further recurrences.